414 Post-stroke Cognitive deficits are associated with reduced cognitive conflict evoked mid-frontal EEG theta oscillations and can be potentially improved with prefrontal transcranial electrical stimulation - Ishita Basu; Alexander Ross; Oluwole Awosika; Francisco Romo-Nava; David Fleck (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: Cognitive dysfunction and/or depressionfollowing ischemic stroke results in loss of independence in daily functioning. The objective of this work is to assess neural correlates of post-stroke cognitive deficits and the effect of left frontal transcranial electrical stimulation on cognitive control and associated brain rhythms. METHODS/STUDY POPULATION: We recorded midfrontal scalp EEG from 15 healthy and 13 participants with stroke while they performed a multi-source interference task (MSIT). The stroke cohort also performed additional MSIT sessions where they received active and sham transcranial direct current stimulation (tDCS) on the left prefrontal cortex (PFC). The EEG was pre-processed to get rid of eye movement and other channel noise artifacts and filtered to retain 0.5-55 Hz components. A Morlet wavelet was used to estimate power in theta (4-8 Hz), alpha (8-15 Hz) and gamma (35-50 Hz) frequency bands over a period of 2 seconds following MSIT image presentation. A generalized linear mixed effects model was used to find effect of group on behavior and EEG oscillations. A GLME was also used to find effects of active tDCS on behavior and EEG. RESULTS/ANTICIPATED RESULTS: We found Group (healthy v stroke) as a significant predictor of both response time (behavior) and conflict evoked theta power in the frontal channels (F1-Fz, F2-Fz). We also found that active tDCS significantly improved MSIT performance as compared to sham, after accounting for cognitive load. Active tDCS also induced low frequency oscillations in frontal EEG channels compared to sham. Preliminary results indicate that mid-frontal theta oscillations are a potential neural correlate of post-stroke cognitive deficit and tDCS of the left PFC might be a promising therapeutic intervention to ameliorate this. DISCUSSION/SIGNIFICANCE: Current therapeutic approaches often do not alleviate post stroke executive dysfunction, hence a better understanding of the brain network changes underlying such deficit can elucidate neural correlates of post stroke cognitive deficit to inform the development of neuromodulation interventions.